2019
DOI: 10.1136/gutjnl-2018-318198
|View full text |Cite
|
Sign up to set email alerts
|

Faecal haemoglobin concentration among subjects with negative FIT results is associated with the detection rate of neoplasia at subsequent rounds: a prospective study in the context of population based screening programmes in Italy

Abstract: ObjectiveTo estimate the predictive role of faecal haemoglobin (f-Hb) concentration among subjects with faecal immunochemical test (FIT) results below the positivity cut-off for the subsequent risk of advanced neoplasia (AN: colorectal cancer—CRC—or advanced adenoma).DesignProspective cohort of subjects aged 50–69 years, undergoing their first FIT between 1 January 2004 and 31 December 2010 in four population-based programmes in Italy.MethodsAll programmes adopted the same analytical procedure (OC Sensor, Eike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 20 publications
5
39
0
Order By: Relevance
“…In line with these results, a recent Spanish study reported an OR for advanced neoplasia of nearly 22 for those with high faecal Hb concentrations (between 10 and 19.9 µg/g faeces) compared with those with low Hb concentrations (between 0 and 3.8 µg/g faeces) 7. Both studies reported risks that were lower than those reported by Senore et al5 This could be explained by the fact that the Italian findings were set against screenees with undetectable faecal Hb concentrations whereas the other studies compared their findings to those with low, yet not undetectable concentrations. The results of this Italian study are also in line with the results from a Dutch CRC screening cohort 8.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…In line with these results, a recent Spanish study reported an OR for advanced neoplasia of nearly 22 for those with high faecal Hb concentrations (between 10 and 19.9 µg/g faeces) compared with those with low Hb concentrations (between 0 and 3.8 µg/g faeces) 7. Both studies reported risks that were lower than those reported by Senore et al5 This could be explained by the fact that the Italian findings were set against screenees with undetectable faecal Hb concentrations whereas the other studies compared their findings to those with low, yet not undetectable concentrations. The results of this Italian study are also in line with the results from a Dutch CRC screening cohort 8.…”
supporting
confidence: 52%
“…The Italian data published in Gut combined with the two previous similar studies from Spain and the Netherlands now firmly establish ground for development of personalised FIT screening strategies using individual actual faecal Hb data 5 7 8. These findings have the potential to help move risk stratification along and to aid public health decision makers in choosing the optimal screening strategy in FIT-based CRC screening.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Alternative approaches to improve transparency of information offered to screening participants could also be explored, such as providing those with a negative result with their numerical f-Hb, so that they themselves are aware of the proximity of their screening result to the threshold. This idea is supported by the findings of a recent study from Italy demonstrating that those with two consecutive negative screening test results, but a cumulative f-Hb above the cut-off for positivity had a significantly increased risk of a future diagnosis of advanced neoplasia [29]. An indication of the individual's proximity to the positivity threshold could be provided alongside strategies applying more intelligent use of FIT, such as varying the length of the screening interval according to f-Hb, with those closest to the threshold offered the opportunity to be screened more regularly than those with very low or undetectable f-Hb.…”
Section: Discussionmentioning
confidence: 57%
“…Another recent proposal is to refer for colonoscopy those patients with cumulative f-Hb concentration ≥20 μg Hb/g faeces over two 'negative' tests. 31 We believe that these data provide the basis to justify a clinical trial in which the risks and benefits of both thresholds could be prospectively compared.…”
Section: Implications For Clinical Practice and Researchmentioning
confidence: 95%